1966
DOI: 10.1029/jz071i015p03705
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of magnetic fields and energetic electrons on the IMP 1 satellite

Abstract: A study of simultaneous magnetic field and energetic particle records from the IMP 1 satellite on the dark side of the earth has shown several distinct correlations that can be understood as diamagnetic effects of charged particle populations. Depression of the magnetic field in the closed magnetic field line configuration of the particle cusp region is observed on most orbits. A small but significant portion of this effect can be attributed to the diamagnetic effects of electrons >45 kev. In the geomagnetic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

1967
1967
1972
1972

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 13 publications
2
24
1
Order By: Relevance
“…Heppner et al [1967] also found that the magnetic field in the region 10-16 R• decreased after the occurrence of a negative bay. Consistent with this evidence, Anderson and Ness [1966] correlated an increase in the electron island fluxes with a deerease in the tail magnetic field. Ness and Williams [1966] and Williams and Ness [1966] observed that the collapse of the high-latitude trapping boundary during magnetic storms was correlated with an increase in the magnetospheric tail field.…”
Section: Introductionsupporting
confidence: 68%
“…Heppner et al [1967] also found that the magnetic field in the region 10-16 R• decreased after the occurrence of a negative bay. Consistent with this evidence, Anderson and Ness [1966] correlated an increase in the electron island fluxes with a deerease in the tail magnetic field. Ness and Williams [1966] and Williams and Ness [1966] observed that the collapse of the high-latitude trapping boundary during magnetic storms was correlated with an increase in the magnetospheric tail field.…”
Section: Introductionsupporting
confidence: 68%
“…It has been known that inside the plasma sheet the magnetic-field magnitude is lower, owing to the diamagnetic effect of the presence of plasma [Anderson and Ness, 1966;Behannon, 1970;Hruska and Hruskova, 1970;Mihalov, 16 12 B()') 8 ß A X 1970], and the direction of the magnetic field is no longer simply directed toward or away from the sun; it has a predominant north-south component [Ness et al, 1967;Behannon, 1970]. Furthermore, the magnetic field ::within the plasma sheet is highly , 1966], but this non-taillike magnetic-field observation was interpreted to mean that the magnetotail did not extend to 60 R• [Ness, 1967].…”
mentioning
confidence: 99%
“…Abrupt magnetic field depressions [292] were observed during energetic (Ee > 30 keV) electron bursts intervals [286,290].…”
Section: The Magnetic Tail Of the Earthmentioning
confidence: 99%